PEMBERDAYAAN MASYARAKAT MELALUI PENGOLAHAN KELAPA MENJADI ARANG DAN KOPRA DI KAMPUNG CIPARAY DESA CITELUK KABUPATEN PANDEGLANG - Ipan, Ipan Saputra; Repi, Repi Rizali (Lembaran Masyarakat: Jurnal Pengembangan Masyarakat Islam, 2023)
Kelapa Coconut has a central role in the lives of the people of Citeluk Village especially in Ciparay, even being a high commodity, considering that the plantation sector is a leading asset in the community Citeluk Village. Since a long time ago, this village was known as the largest coconut producer in Pandeglang Regency until it was dubbed as Citelukalapa Village, but the people in Citeluk Village were still not able to maximize the potential of the coconut properly. Along with the development of community initiatives, the people of Citeluk Village began to process coconuts to be more varied, one of which was processing coconuts into copra and the waste from the coconut fruit was used to make charcoal. The purpose of this study was to determine the process of community empowerment through processing coconut into copra and charcoal. The method used in this research is qualitative. Data collection techniques used are observation, interviews, and documentation. The result of this research is that the empowerment of the community in Citeluk Village in processing coconut into copra and charcoal can increase welfare (income).